« Une splendide anomalie ? », le Pilgrim’s Progress de Ralph Vaughan Williams - Gilles Couderc (Revue LISA)
First performed on April 26, 1951, at Covent Garden, four–act opera Ralph Vaughan Williams’s The Pilgrim’s Progress after John Bunyan’s eponymous Christian allegory, was then called “a magnificent anomaly” by the composer’s colleague Rutland Boughton, and continues to garner the same criticism as then : “beautiful music but not theatrical enough”. While the composer was conscious of the atypicality of his “operatic morality” it is indeed surprising to see an avowed agnostic composer spend forty years of his life on a work that dismisses the conventions of traditional opera and endeavours to portray mystical experience on stage and to renew with the sense of rite and ritual, part and parcel of the genre as Wagner’s subtitle for his Parsifal, “a sacred scenic festival”, reminds us.